PROFITABILITY OF ISLAMIC COMMERCIAL BANKS IN INDONESIA: DETERMINANTS AND IMPLICATIONS - Fitria, Cahyani Wulan; Setiawan, Agus (UIN Sunan Gunung Djati Bandung, 2025)
The performance of Islamic Commercial Banks (BUS) in Indonesia is faced with significant challenges related to global economic fluctuations, the COVID-19 pandemic, and the industrial transformation of the merger of Bank Syariah Indonesia (BSI). This observation aims to guess the profitability factor (ROA) of BUS focusing on macroeconomic variables (Inflation, GDP, BI7DRR) and internal bank variables (CAR, BOPO, NPF, and FDR) within 2019-2023. Quantitative methods are suitable to be applied using multiple linear regression analysis with secondary panel data from 11 BUS samples, annual financial data of BSI before and after merging are included using the pronorma method, resulting in 55 sample results then processed with IBM SPSS 29 tools. It was found that GDP and CAR have a significant positive effect on ROA. BOPO and NPF have a significant negative effect on ROA. Inflation, BI7DRR, and FDR have no significant Impact on ROA. The resulting presentation of 87.3% of the above variables affects profitability, while the rest is generated from variables outside the study. These findings reinforce the importance of controlling asset quality, capital strengthening, and operational efficiency in increasing BUS profitability in Indonesia. The government also needs to make strong regulations for the sustainability of Islamic financial institutions, especially Islamic banking. This research practically provides recommendations to policymakers to strengthen regulations related to asset quality, and operational efficiency. The inclusion of BSI analysis before and after the merger, can provide broad, unique, and impactful insights into restructuring in the context of Islamic banking in Indonesia.